Geographic patterns of prescription opioids and opioid overdose deaths in New York State, 2013-2015. (1st February 2019) - Romeiser, Jamie L.; Labriola, Jake; Meliker, Jaymie R.
Highlights: Spatial patterns in opioid prescription rates and mortality rates exist within NYS. Prescription and mortality clusters do not overlap. Small reductions in the number of prescriptions may not decrease mortalities. Abstract: Objectives: To examine the relationship between prescription opioid rates and prescription opioid overdose deaths using spatial cluster and regression analyses. Methods: Publicly available county-level data were obtained from the New York State Health Department and the Centers for Disease Control and Prevention, 2013–2015. Kulldorff's spatial scan statistic was used to investigate spatial clustering of New York State opioid prescription overdose death rates, as well as opioid prescription rates. A Poisson regression was used to analyze opioid prescriptions as a predictor of mortality accounting for spatial autocorrelation in the residuals. Results: We report 1440 overdose mortalities and 26.8 million opioid prescriptions throughout New York State in 2013–2015. Multiple significant clusters were found for both opioid prescription mortalities as well as prescriptions, although the locations of the elevated rates did not strongly overlap. Poisson regression showed a significant, small, negative relationship between prescriptions and opioid mortalities, wherein for every 10, 000 prescriptions increased, the number of opioid mortalities decreased approximately 0.12%; therefore, essentially a null relationship. Conclusions: Simply reducing the number of prescriptions may not be effective in reducing prescription related mortality; although opioid prescription dosing information should be made available to engender a better evaluation of the epidemic. Geographical differences in opioid mortalities exist above and beyond what can be explained by prescription rate data; identifying these locations may help inform and guide public health interventions. Despite the recent reduction in opioid prescription rates, the overall population is still inundated with prescriptions.